Rheological, Textural, And Sensory Evaluation Of Texture-Modified Rice Porridge For Patients With Dysphagia - Yong, Hui Yin (2019)
Dysphagia is defined as the difficulty or inability to swallow food and liquid. Pureed food, a class of texture-modified food is commonly used in dysphagia management. Patients with dysphagia can benefit from this diet prescription because it requires minimal oral preparation and manipulation. To date, only few studies focused on the rheological properties of dysphagia-oriented pureed foods compared to thickened beverages. During the preparation of pureed food, commercially available thickener is usually added to impart desired consistency, which aids in reducing the risk of choking. However, high cost and limited availability of commercial thickener are burden for some patients. Therefore, this study was carried out to evaluate the effects of different starches (tapioca and sago) and gums (xanthan and guar) at different concentrations (1, 2, and 3% based on total weight of ingredients) on rheological and textural properties of pureed rice porridge. The thickening of pureed rice porridge with 1% gum and 2% starch produced samples with close apparent viscosity to the reference sample (commercial dysphagia-oriented rice porridge product). All pureed samples with similar viscosity showed variation in behaviors during rheological and textural measurements. After selection of suitable concentration for each thickener (1% gum and 2% starch), the pureed rice porridge samples were then dried using hot air dryer (80ºC for 3 hours) to produce instant rice porridges. The developed products were tested for their physicochemical, pasting, rheological, and textural properties.